1989
DOI: 10.1002/cyto.990100406
|View full text |Cite
|
Sign up to set email alerts
|

Problem of size dependence in fluorescence DNA cytometry

Abstract: The relationship among fluorescence intensity, area, thickness, and DNA concentration of DNA-bearing polyacrylamide film, stained with 50 ng/ml DAPI, was studied using an epi-illumination cytofluorometer. Measurements and theoretical analysis suggest the inevitability of the size-dependent effect on human cell nuclei in which the order of the DNA concentration is approximately 10 mg/ml, and that this effect can be virtually negated if the nuclei are stretched and flattened to less than 0.33 pm in thickness on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We had previously observed in acetonelmethanol-fixed cells that no significant cell-size dependencies of IO1 were present over a broad range of PI concentrations (1-200 pglml). This indicated that concentration-dependent quenching or inner filtering effects were not present at the concentrations used (22).…”
Section: Discussionmentioning
confidence: 92%
“…We had previously observed in acetonelmethanol-fixed cells that no significant cell-size dependencies of IO1 were present over a broad range of PI concentrations (1-200 pglml). This indicated that concentration-dependent quenching or inner filtering effects were not present at the concentrations used (22).…”
Section: Discussionmentioning
confidence: 92%
“…In high‐resolution observation conditions (NA = 1.3), the distribution of illumination intensity shows a partial confocal effect due to the limited illumination field (29). This effect causes the nonhomogeneous illumination of the three‐dimensional sample as function of the focal position at which the optical section was acquired and the dependence on the three‐dimensional extension of the sample if it exhibits different size (30). The sample fraction that is within the depth of field of the lens, and consequently the bidimensional projected image, is dependent on the sample three‐dimensional size (30).…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The fluorescence intensity, I, of light emitted perpendicularly to the incident plane by an object of height d can be expressed (30) by the following equation: where I 0 , A , η, k , and c are intensity of the excitation light, projected area of the sample, emission yield, absorption coefficient, and concentration of the substance in the sample, respectively. Therefore, when we want to estimate the average concentration (c) of a molecule (e.g., DNA) in samples of different sizes, which have been labelled with a selective probe (DAPI in our case), a simple direct evaluation of the fluorescence intensity is not sufficient if the analysis is performed by high‐resolution conventional wide‐field microscopy (generally, the conditions of the sample and the flow cytometry setup are optimized, at low resolution, to have the entire three‐dimensional sample within the depth of field of the lens in order to perform integral intensity measurements correctly).…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The concentrations of DNA in bacteria are several times the concentration found in human diploid nuclei (1%, by volume) (25) and are sufficient to give measured attenuation of DAPI-DNA fluorescence in the larger aquatic bacteria (10) of up to 10%. Distances are too great for resonance energy transfer (13), but the complex could absorb reemitted photons.…”
mentioning
confidence: 92%